Private-sector investment in African agricultural research - Byerlee, Derek; Nagarajan, Latha; Pray, Carl E. (International Food Policy Research Institute, 2016)
This chapter provides an overview of private agricultural R&D in SSA. The approach is not comprehensive, but is analyzed through a series of case studies. The next section provides an overview of three types of private agricultural R&D and their main drivers as a preamble to a more detailed case study review centered on the typology. Thereafter, the discussion focuses on policies needed to realize the potential of private African agricultural R&D into the future, before providing final conclusions.